2002
DOI: 10.1046/j.1432-1327.2002.02817.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a functional requirement for isoprenylation by the human prostacyclin receptor

Abstract: In the current study, we have established that the human (h) prostacyclin receptor (IP) is isoprenylated in whole cells. Through site directed mutagenesis and generation of the isoprenylation defective hIP SSLC , it was established that while isoprenylation of hIP does not influence ligand binding, it is obligatory for agonist activation of adenylyl cyclase and cAMP generation. Overexpression of Ga S significantly augmented cAMP generation by the hIP but not by the hIP SSLC . Moreover, Ga S co-immunoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 39 publications
(60 reference statements)
6
64
0
Order By: Relevance
“…It has been suggested that regulated cycles of palmitoylation/depalmitoylation, such as in response to agonist, may result in the formation of a transient fourth intracellular loop (IC 4 ) to regulate receptor-G protein coupling, downregulation, and/or internalization, to list but a few processes. More specifically, in the case of the hIP, in addition to its established isoprenylation (24,25), it undergoes palmitoylation at Cys 308 and Cys 311 in response to stimulation with the selective IP agonist cicaprost (2 h), whereas Cys 309 was found not to be palmitoylated under those conditions (27). Because the proposed RBD contains Cys 308 and Cys 311 that are known to undergo palmitoylation, in addition to Cys 309 , the current study sought to investigate the role of those Cys residue(s) and the possible influence of palmitoylation on the interaction between the hIP and Rab11a and to identify the key structural determinants of the RBD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that regulated cycles of palmitoylation/depalmitoylation, such as in response to agonist, may result in the formation of a transient fourth intracellular loop (IC 4 ) to regulate receptor-G protein coupling, downregulation, and/or internalization, to list but a few processes. More specifically, in the case of the hIP, in addition to its established isoprenylation (24,25), it undergoes palmitoylation at Cys 308 and Cys 311 in response to stimulation with the selective IP agonist cicaprost (2 h), whereas Cys 309 was found not to be palmitoylated under those conditions (27). Because the proposed RBD contains Cys 308 and Cys 311 that are known to undergo palmitoylation, in addition to Cys 309 , the current study sought to investigate the role of those Cys residue(s) and the possible influence of palmitoylation on the interaction between the hIP and Rab11a and to identify the key structural determinants of the RBD.…”
Section: Discussionmentioning
confidence: 99%
“…The IP is primarily coupled to G s /adenylyl cyclase activation but may regulate other effectors in a cell-and/or species-specific manner (23,24). The IP is somewhat unusual among GPCRs in that it undergoes both isoprenylation and palmitoylation within its carboxyl-terminal tail (C-tail) domain, modifications that are critical for its signaling and function (24 -30).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The IP is somewhat unusual among GPCRs in that it undergoes isoprenylation and palmitoylation within its carboxyl-terminal tail (C-tail) domain, modifications critical for IP signalling and function 96-100 . More specifically, the human IP undergoes farnesylation at Cys 383 within its carboxy-terminal conserved -C 383 SLC 386 , or 'CaaX', motif 99,100 and palmitoylation at Cys 308 , Cys 309 , and Cys 311 (Figure 6) 97,98 . While neither lipid modification affect the ligand binding properties of the IP, they modulate its G protein coupling/intracellular signalling and, in the case of palmitoylation, may influence its ability to directly interact with Rab11a, to regulate agonist-induced trafficking of the IP following activation [96][97][98][99] .…”
Section: Regulation Of Ip Signalling Through Novel Protein:protein Inmentioning
confidence: 99%